Different Kinds of Prototyping and Generator Tools to Develop Analytics Information System - Sulianta, Feri; Fauzi, Esa (International Journal of Psychosocial Rehabilitation, 2020)
Analytical tools and datamining tools can be used intended to learn the characteristics of the database that is owned, including also looking for data requirements that will later be used as a basis for building information systems that have analytical features such as decision support systems or executive information systems. In this case, the use of analytical tools is included in the ’observation stage’ in the first stage of the system life cycle, which is to use analytical tools for exploration before actually modeling the system. OLAP tools can be used as prototypes for analyst systems and also for users so users can see before the system with analytic features is created. This paper explains how to use the tool in uncovering findings on data that will be used as a basis for building systems that have analytical features, such as executive information systems, decision support systems, or expert systems.